2018
DOI: 10.1007/s00403-018-1833-9
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of lactic acid sensations in sensitive skin by stimulating the barrier function and improving the ceramide profile

Abstract: We determined whether compensating ceramides in the stratum corneum (SC) may ameliorate the impaired barrier function and subsequently attenuate the enhanced skin sensitivity. Treatment for 4 weeks with the ceramide complex cream or the placebo cream significantly ameliorated the intensity of lactic acid sensations in 39 female subjects with sensitive skin, the degree of which was attenuated to a greater extent at 1 week by the ceramide complex cream compared with the placebo cream. The amelioration of skin se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Fan Linna et al found that sebum secretion in the sensitive skin (SS) group was lower than that in the nonsensitive skin (NS) group, suggesting that the development of SS might be associated with sebum secretion and its specific components . Nojiri H et al found that stimulating the barrier function and improving the ceramide profile could improve the lactic acid sensitivity in sensitive skin . We found in oily skin groups the correlation between skin sensitivity and eating spicy food as well as sleeping time in the past week was statistically significant ( P < .01), while in neutral skin groups there were significant correlations between the sleeping time and sleeping quality with skin sensitivity ( P < .01).…”
Section: Discussionmentioning
confidence: 60%
“…Fan Linna et al found that sebum secretion in the sensitive skin (SS) group was lower than that in the nonsensitive skin (NS) group, suggesting that the development of SS might be associated with sebum secretion and its specific components . Nojiri H et al found that stimulating the barrier function and improving the ceramide profile could improve the lactic acid sensitivity in sensitive skin . We found in oily skin groups the correlation between skin sensitivity and eating spicy food as well as sleeping time in the past week was statistically significant ( P < .01), while in neutral skin groups there were significant correlations between the sleeping time and sleeping quality with skin sensitivity ( P < .01).…”
Section: Discussionmentioning
confidence: 60%
“…Sensitive skin is an abnormal subclinical sensory response that includes tingling, tightness, burning or prickling, and possibly pain or itching that may be caused by medications, cosmetics, and toiletries, but without obvious symptoms [20]. In fact, people of different ages and genders have different levels of exposure to such irritants in different working or living environments, which may affect the development of sensitive skin symptoms [21].…”
Section: Discussionmentioning
confidence: 99%
“…“Sensitive skin (SS)” is defined by a special interest group, the International Forum for the Study of Itch1, 1 as skin that develops an uncomfortable sensation in reaction to stimuli that skin should not normally react to various pathophysiological mechanisms are thought to be implicated in sensitive skin development 2 . Neuropathy‐like discomfort sensations, such as burning, stinging, pain, and itching, are characteristic features of sensitive skin; therefore, it is postulated that a neurosensory disorder accompanied by epidermal barrier dysfunction plays a significant role in the pathogenesis of SS 3,4 …”
Section: Introductionmentioning
confidence: 99%